Potential Distribution of Three Agricultural Crops in Costa Rica Under Scenarios of Climate Change: Implications of Agroforestry Management and Socio-Economical Development - Coto Fonseca, Alberto (2017)
The applied study of climate change on human activities has gained relevance in recent years. Its effect over the agricultural zones of developing countries is important to establish future adaptation strategies. In this work, current and future potential distributions under the framework of niche modeling of rice, sugarcane and pineapple for Costa Rica were evaluated. The results suggest that, for all three crops, the areas with higher probability of a negative effect due to the change in distribution of suitable areas correspond to rural environments. The point variations in mean annual temperature and annual precipitation variables did not show a defined pattern in the distribution areas of the crops. Regarding the overlapping effect between production areas and the forest area of the country, sugarcane presents the greatest overlapping in all future scenarios, while pineapple cultivation shows an inverse trend. The actual investigation proves the importance of climate change scenarios as a tool for evaluating the potential effect of this phenomenon over agricultural crops, with its repercussions at social and environmental level.